Practicing Citizens: Adult Stories of Cocooning and Taking Flight - D. Ann Tunmer (Adult Education Research Conference, 2000)
This qualitative study concerns how a specific vehicle for social intervention programs impacts upon the civic behavior of targeted individuals. The crux of the problem is whether individuals can learn citizenship, and, if provided the skills and opportunities, will citizens utilize their knowledge to participate politically.